"Clicking" Porphyrins to Magnetic Nanoparticles for Photodynamic Therapy. Issue 1 (23rd October 2013) - Thandu, Merlyn; Rapozzi, Valentina; Xodo, Luigi; Albericio, Fernando; Comuzzi, Clara; Cavalli, Silvia
Abstract A method for the preparation of superparamagnetic iron oxide nanoparticle–porphyrin (SPION‐TPP) conjugates through click chemistry, which can be used as novel theranostic nanoagents for photodynamic therapy is developed. The synthesis, characterisation, and evaluation of the photocytotoxicity profiles of the nanoconjugates prepared is reported. Upon light irradiation, SPION‐TPP nanoconstructs promote a photodynamic effect in vitro in murine amelanotic melanoma B78‐H1 cells, with IC50 values in the region of 800 nM, similarly to unbound TPP, whereas they remain non‐cytotoxic in the dark. However, these nanoconstructs show poor cellular uptake, which influences a linear dose–response effect. Therefore, the improvement of delivery to cells has also been studied by conjugating a well‐known cell‐penetrating peptide (TAT peptide) to the SPION‐TPP nanoparticles. The new nanoconstructs show lower IC50 values (in the region of 500 nM) and a clear dose–response effect. Our results suggest that TAT‐conjugated SPION‐TPP nanoparticles are efficient nanodevices both for tracking drugs by means of magnetic resonance imaging (MRI)‐based techniques and for treating cancer cells through photodynamic therapy, thus functioning as promising theranostic nanoagents.